2008
DOI: 10.1097/mol.0b013e328306a057
|View full text |Cite
|
Sign up to set email alerts
|

Glycation as an atherogenic modification of LDL

Abstract: Glycation of LDL occurs chiefly due to the nonenzymatic reaction of glucose and its metabolites with the free amino groups of lysine in which LDL is rich. Higher concentrations of glycated LDL are present in diabetic than in nondiabetic individuals, but even in the latter, there is generally more circulating glycated LDL than oxidatively modified LDL. Probably, oxidation and glycation of LDL are at least partially interdependent, but both prevent LDL receptor-mediated uptake and promote macrophage scavenger re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 80 publications
1
57
0
8
Order By: Relevance
“…LAL lysosomal acid lipase, SMC smooth muscle cells, TO TO901317, LXR agonist, RSG rosiglitasone, PPAR-gamma agonist. **P \ 0.01 molecules and scavenger receptors [1,16,26]. Our data extend these findings, revealing another effect of gLDL, namely the down regulation of LAL expression in SMC.…”
Section: Discussionsupporting
confidence: 81%
“…LAL lysosomal acid lipase, SMC smooth muscle cells, TO TO901317, LXR agonist, RSG rosiglitasone, PPAR-gamma agonist. **P \ 0.01 molecules and scavenger receptors [1,16,26]. Our data extend these findings, revealing another effect of gLDL, namely the down regulation of LAL expression in SMC.…”
Section: Discussionsupporting
confidence: 81%
“…43 Furthermore, in patients with DM and dyslipidemia, glycation of apoprotein A attenuates the atheroprotective function of highdensity lipoprotein, and, in contrast, glycation of apoprotein B reinforces the low-density lipoprotein-induced inflammatory response. 44, 45 Thus, diabetic pathophysiology promotes an antiangiogenic process and meanwhile mitigates pro-angiogenic …”
Section: Discussionmentioning
confidence: 99%
“…The relative resistance of LDL to glycation in vitro, indicated by the requirement for its exposure to supraphysiological concentrations of glucose for longer than its physiological circulating half-life, has been consistently reported. 33,[55][56][57] In a recent review, 10 earlier investigators reported employing glucose in the range 25-500 mmol/L for periods of up to 28 days and in the presence of elemental oxygen. The implication is that glycation occurs more readily in vivo.…”
Section: Discussionmentioning
confidence: 99%